The Relationship of Parenting With Emotional Intelligence - Iska, Pera; Clara, Felicya; Silvianetri, Silvianetri; Cristin, Angeline (Darussalam: Journal of Psychology and Educational, 2022)
The main problem in this study is that parents have provided guidance, education, and nurture their children, but students still find the inability to recognize their own emotions, recognize the emotions of others, motivate themselves, and build relationships with others. The purpose of this study was to determine the relationship between parental parenting and emotional intelligence in students at SMP 4 Lintau Kec.Lintau Buo Utara, Tanah Datar Regency. The type of research that researchers use is a type of quantitative research with a correlational method. The population in this study was students of grades VII, VIII of SMP 4 Lintau Kec.Lintau Buo Utara, Tanah Datar Regency, which was 40 students. The type of sampling in this study was using the Solvin formula, so that the number of samples in this study was 36 students. The data collection technique is to provide a questionnaire. The data in this study were tested using product moment analysis with a significant value of 0.004<0.05 so that the two variables had a significant relationship. The better the parenting style owned by the students, the higher the emotional intelligence possessed by the students of SMP 4 Lintau Kec Lintau buo north of Tanah Datar District.